ANALYSIS OF OPTICAL-ENERGY CHARACTERISTICS OF SOLAR THERMAL POWER PLANTS WITH MIRROR CONCENTRATION SYSTEM USING NUMERICAL METHODS - Soliyev, Bobonazar Gulomjon ugli (Educational Research in Universal Sciences, 2023)
In this regard, the purpose of this topic is to develop calculation methods (numerical experiments) and, on this basis, to establish the distribution patterns of the concentrated current in the focal plane and on the surface of the receiver. Also considered are such issues as the development of a methodology for calculating the systems of storage devices with receivers and steam generators, taking into account concentration uncertainties.